Cover Feature: Physico‐Chemical Modeling of a Lithium‐Ion Battery: An Ageing Study with Electrochemical Impedance Spectroscopy (Batteries & Supercaps 6/2019). Issue 6 (31st May 2019) - Heinrich, Marco; Wolff, Nicolas; Harting, Nina; Laue, Vincent; Röder, Fridolin; Seitz, Steffen; Krewer, Ulrike
Abstract : The Cover Feature shows aging lithium‐ion batteries on a timeline each with a digital half in binary code visualising a battery model. Impedance spectroscopy is applied comparing measurement and simulation results. More information can be found in the Article by M. Heinrich et al .